Promising millet production and processing technologies in rainfed areas - Chapke, Rajendra R (Indian Farming, 2023)
Many millet production technologies are available with research organizations which need to be evaluated in farmers’ fields for their wider adaptability. For this, an initiative was taken by the ICAR-IIMR, Hyderabad under farmer FIRST project wherein improved practices gave substantially higher yields and net returns compared to existing farmer’s practices especially from de-hulled finger millet and little millet grains which fetched up to 2–5 times more profit. Backyard farming with improved breed of poultry birds and goat gave additional income. Diversification of millet-based farming should be encouraged to reach targeted productivity and profitability with support from government policies. Latest knowledge, timely input support and promotion of valueaddition of millets through group approach were found to be the key elements in millets value-chain development.